COVID-19 STRESS AND MENTAL HEALTH: HOW PERCEIVED SOCIAL SUPPORT MITIGATES IMPACT - Reyes , Luisa Santos (Ayden International Journal of Education and Social sciences, 2024)
The COVID-19 pandemic has had a profound impact on various aspects of life in the Philippines, affecting the economy, physical health, and mental well-being. This global health crisis has led to increased anxiety and psychological distress among healthcare professionals and the general population. As of July 9, 2021, there have been 1,455,585 confirmed COVID-19 cases and 25,650 deaths in the Philippines, highlighting the significant burden of the virus. Healthcare institutions, particularly for frontliners, have become high-risk environments due to the additional workloads and increased exposure to health hazards. This situation has taken a toll on the mental health of medical professionals. Studies from other countries, such as Albania and Germany, during previous pandemics have also reported anxiety and psychological distress among healthcare workers and patients. This crisis underscores the importance of identifying and addressing the immediate psychological needs of patients and healthcare professionals. Understanding the mental health challenges arising from the pandemic is crucial for developing effective strategies and support systems to mitigate the psychological impact.